Tax incentives, bequest motives, and the demand for life insurance: Evidence from two natural experiments in Germany - Nicolas Sauter; Jan Walliser; Joachim Winter (Center for Economic Studies and ifo Institute (CESifo), 2010)
Whole life insurance plays an important role in household saving. However, empirical evidence on its determinants is scarce. This paper studies two natural experiments to identify the effects of tax incentives and bequest motives on life-insurance demand. An unanticipated tax reform in 2000 halved the tax exemption limit for capital income in Germany. We document that the demand for life insurance reacted strongly to this change. With regard to bequest motives, we analyze the demand for life insurance in the former German Democratic Republic (GDR). Relative to market-based economies, the socialist GDR can be viewed as an experimental institutional setting where life-insurance demand was not influenced by tax considerations which allows us to isolate bequest motives while controlling for life-cycle and precautionary motives. We find a significantly higher ownership probability among households with children and a high regard for the family, confirming bequest motives in life-insurance demand.
Keywords: D91; C25; D14; G11; 330; savings; life insurance; capital income taxation; bequests; Lebensversicherung; Nachfrage; Sparen; Anlageverhalten; Erbe; Kapitalertragsteuer; Steuerwirkung; Feldforschung; Deutschland; Vergleich; DDR